Estudo retrospectivo de enteroparasitoses em indivíduos com HIV-1/AIDS na era HAART em hospital Escola de nível quatenário - Cardoso, Luciana Ventura (2011)
Was described the epidemiology of intestinal parasites in patients from an AIDS reference service in the northeastern São Paulo, Brazil Retrospective evaluation of all HIV-1/AIDS positive patients whose Hospital de Base/São José do Rio Preto laboratorial analysis was positive for enteroparasites after diagnosis of HIV-1 infection, from January 1998 to December 2008. Statistical analysis was performed using version 2.4.1 statistical software R. The level of significance adopted was 5%. The most frequent protozoan was Isospora belli (4.20%), followed by Giardia lamblia (3.5%), Entamoeba coli (2.80%) and Cryptosporidium parvum (0.28%). The Ancylostoma duodenale was the most helminths frequently detected (1.40%), while Taenia saginata and Strongiloides stercoralis were found in 0.7% of the samples. Results showed that diarrhea was significantly associated with giardiasis and isosporiasis. However, no association was observed between CD4+ cell counts, viral load and the characteristic of any particular parasite. Our data may serve as a starting point for further comparisons with various Brazilian regions and other developing countries. The data may provide important clues to the future understanding, prevention and control of enteric parasites around the world.